THE RELATIONSHIP BETWEEN WORK–LIFE BALANCE, STRESS LEVELS, AND EMPLOYEE TURNOVER WITH ORGANIZATIONAL CULTURE AND SOCIAL SUPPORT AS MODERATING VARIABLES (A CASE STUDY OF THE EXPORT–IMPORT DEPARTMENT EMPLOYEES AT PT TJIWI KIMIA) - Aulia Ramadhani; Arief Noviarakhman Zagladi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the relationship between work–life balance (WLB), employee stress levels, and turnover, while investigating the moderating roles of organizational culture and social support. Conducted among employees in the export–import department of PT Tjiwi Kimia, this research employs a quantitative survey approach. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate inter-variable relationships. The findings indicate that WLB significantly reduces employee stress and turnover. These effects are strengthened by a supportive organizational culture and adequate social support, both of which significantly moderate the relationships between WLB, stress, and turnover. The results support role balance theory and social support theory, emphasizing that employee well-being depends not only on balancing professional and personal life but also on a supportive work environment. Practically, the study suggests that organizations should strengthen flexible WLB policies, foster a supportive organizational culture, and facilitate social support systems as effective strategies to enhance employee well-being and retention.